Psicanálise e câncer: leitura psicanalítica de um caso de leucemia - Chiarella, Andréa (2017)
Somatic manifestations and the processes involved are increasingly present in the psychoanalytic clinic. In this way, the body becomes a place of flow for emotions and affections that could not be elaborated psychically. Always in search of a better understanding of what happens with cancer patients, especially those affected by leukemia, I propose in this work a reflection about the possible relation between initial environment, early trauma and the outbreak of cancer in adult life. Through the study of the clinical case of a patient affected by acute leukemia, I seek to gather clinical experience, research and theory, according to the model postulated by Freud, to think of more comprehensive models of clinical management in the treatment of these cases